MATLAB Programming for Engineers. - Stephen J Chapman (Cengage Learning, 2004)
Emphasising problem-solving throughout, this successful title introduces the MATLAB language and shows how to use it to solve typical technical problems. It demonstrates how to write clean, efficient, and well-documented programs and how to locate any desired function with MATLAB's online help facilities.